Vibration-based structural change identification of multi-storied reinforced concrete building using sensitivity-based model updating technique - Ghimire, Jhabindra P.; Matsumoto, Yasunao; Nattapong, Areemit; Yamaguchi, Hiroki (Nepalese Journal of Engineering, 2005)
The applicability of the sensitivity-based model updating technique to the identification of structural changes made in an existing structure was investigated with a pile supported reinforced concrete building undergoing major renovation. Seven different renovation stages which represented the different states of the building during the renovation were considered. The modal properties, i.e., natural frequencies and mode shapes, identified from the ambient vibration measurement of the building were used in the identification of structural changes. The sensitivity-based model updating technique was used to update the mathematical models of the building for all renovation stages. Structural change made in the building during renovation was quantified in terms of structural parameters identified from the model updating. More than 50% reduction in stiffness in the longitudinal direction of the building was found significant in all four story of the building, which may be attributed to the removal of shear walls. The storey stiffness obtained form the model updating was compared between before and after the renovation. Keywords: ambient vibration, mathematical model, sensitivity-based model updating, building renovation, structural change Nepalese Journal of Engineering Vol.1(1) 2005 pp.51-63